Pengaruh Literasi Digital Terhadap Sikap Kewargaan, Perilaku Ekonomi, dan Komunikasi Matematis Siswa di Era Society 5.0 di SMK Negeri 1 Pematangsiantar - Putri, Risma Aprilia; Adsari, Juwita Dwi; Rumahorbo , Alfredo Totadoi; Siahaan, Rotua; Silalahi, Ayel Febriyani; Pangaribuan, Firman (Polinomial : Jurnal Pendidikan Matematika, 2026)
Digital literacy is a key 21st-century competency that plays a crucial role in shaping ethical, adaptive, and productive digital citizens. This study aims to analyze the influence of digital literacy on civic attitude, economic behavior, and mathematical communication skills of students in the Society 5.0 era. A quantitative approach was employed involving 302 students of SMK Negeri 1 Pematangsiantar, selected through stratified random sampling from a total population of 881 students. The research instrument was developed based on digital literacy theory and previous studies, while data were collected through a closed-ended questionnaire using a five-point Likert scale. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS software. The findings revealed that digital literacy has a positive and significant effect on civic attitude (path = 0.741), economic behavior (path = 0.539), and mathematical communication skills (path = 0.384). The R² values of each construct indicate that the model has a strong explanatory ability for the endogenous variables, while CA, CR, and AVE values confirm high construct reliability. Discriminant validity was also met according to the Fornell–Larcker and HTMT criteria. These results highlight that digital literacy not only reflects technological proficiency but also contributes to shaping responsible citizenship, wise economic behavior, and mathematical communication skills relevant to the learning needs of the Society 5.0 era.